SERVIÇO DE ATENDIMENTO MÓVEL DE URGÊNCIA – SAMU: PERFIL DOS ATENDIMENTOS, POTENCIALIDADES, FRAGILIDADES E ESTRATÉGIAS - Orsolin, Leonardo Londero (2019)
The Unified Health System (SUS) is considered one of the largest public health systems in the world. Through its principles and guidelines, it guarantees access to health as the right of every Brazilian citizen. In this direction, the Ministry of Health (MS) released, in 2003, the National Urgency and Emergency Policy, with the purpose of structuring and organizing the urgency and emergency network in the country. Thus, the present study aimed to characterize the profile of care provided by the mobile emergency care service - SAMU, in the central region of Rio Grande do Sul state, as well as identify the potentialities, weaknesses and strategies experienced/suggested by the users of this service. This is a retrospective, qualitative, descriptive, exploratory and quantitative study. Data were collected from January 2017 to March 2019. In the quantitative approach step, documentary data from the SAMU service in the central region of RS state were used. The qualitative approach step, in turn, occurred through individual interviews with users previously attended by the service. The results show that 15,445 events were attended, with a predominance of clinical events (7,357), followed by trauma (4,841), of which neurological events (1,775) and collisions trauma (2,034) stand out. The response time of the visits was 13.5 minutes in the months evaluated, and the recommended is 12 minutes. Qualitative data resulted in three categories regarding the potentialities of SAMU; three categories related to weaknesses and two categories regarding strategies for SAMU qualification. The analysis of the profile of care provided by the Mobile Emergency Care Service concludes that, compared to larger cities, it attends a significant number of events (8,226 in 2017 and 7,219 in 2018), mostly clinical care, predominantly neurological events, followed by traumatic care, of which collisions. Although the service has important potentials related to the access and competent performance of the multidisciplinary team, weaknesses associated with inadequate conditions of vehicles and highways, the delay in the arrival of care at the event venue, among other specific aspects, remain. The strategy is to set up a local regulation center in order to minimize the arrival time of the service to the event venue. This study contributed to the qualification of the emergency care network of the municipality and the region.